Особливості формування та удосконалення соціально-психологічного клімату у підприємницьких структурах - Liubov, Vodianka; Kobelia, Zoriana (My University, 2023)
The article reveals the concept and features of the formation of the social and psychological climate in entrepreneurial structures, and highlights its components. A number of factors determining the general mood in the team were analyzed. It was also etermined that the main conditions necessary for the formation of a healthy atmosphere at the enterprise are: established communication, organized information flows, an organized self-management system, joint setting of goals and the availability of opportunities to achieve them. The impact of various socio-psychological management methods on the effectiveness of employees' performance of assigned tasks is predicted. The article provides a number of reliable, psychodiagnostic, sociometric methods (V.F. Rakhivskyi's "Communication" method, A.F. Fiedler's "Diagnostics of the psychological atmosphere in the organization", A.M. Lutoshkin's "Map-scheme for determining the psychological climate in the team"), thanks to which it is possible to investigate the level of social and psychological climate in the team. The program for improving the existing social and psychological climate in the team is presented, which consists of a set of measures, which in turn are tools for increasing the productivity of the enterprise and contribute to the achievement of its strategic goals. Effective and efficient methods of directly solving the problem of an unfavorable social and psychological climate are presented, namely: team building, retraining, conducting psychological webinars, creating a comfortable working environment, organizing various types of corporate events, introducing and practicing gamification.According to the analysis of the views of modern scientists, various methods of solving the problem of an unfavorable social and psychological climate are presented. It was determined that a healthy social and psychological climate, which is extremely favorable for the effective operation of the enterprise, is primarily ensured by harmonious relations between employees, mutual respect, the authority of management, care for employees and the creation of the best conditions for their activities, psychological compatibility of employees, the similarity of their interests and views on life.
FEATURES OF THE FORMATION AND IMPROVEMENT OF THE SOCIAL AND PSYCHOLOGICAL CLIMATE IN BUSINESS STRUCTURES
Keywords: соціально-психологічний клімат; підприємство; колектив; управління персоналом; соціально-психологічні методики